Financing Cities : Fiscal Responsibility and Urban Infrastructure in Brazil, China, India, Poland and South Africa - Clarke Annez, Patricia (New Dehli : Sage Publications and World Bank, 2012)
This book, Financing cities, emphasized case studies on different topics to look at the interactions of a range of variables and factors and to see how they fit together. Rather than require each case to follow the same format, the authors have structured their papers around the issues that matter most from their perspective in addressing the topic in hand. The first part of this book presents case studies describing the framework established at the national level to promote urban infrastructure finance while ensuring fiscal discipline and reviewing recent experience as well as future challenges. The subjects covered include the impact of political and fiscal decentralization, limitations on borrowing, managing moral hazard, the role of the financial sector, the achieving of the right balance between stringent controls and encouragement of local governments taking responsibility for fiscal discipline coupled with market discipline. The cases featured include three of the world's largest decentralized nations; together the five countries featured in the conference account for nearly a third of the world's urban population. Part I includes case studies for each of the five countries featured in the conference: Brazil (Chapter 1), China (Chapter 2), India (Chapter 3), Poland (Chapter 4) and South Africa (Chapter 5). Part II then shifts from the frameworks for fiscal discipline to urban infrastructure investments and the strategies used to mobilize investment funding. Chapters 6 and 7 examine the financing strategies for urban infrastructure in Shanghai and Brazil respectively. The next two chapters focus on specialized intermediaries offering urban infrastructure finance in cities. One is a fully private venture in South Africa (Chapter 9) while the other, in Tamil Nadu, India (Chapter 8), is a spin-off of a government fund with minority private ownership. The final two chapters examine experiences with two other mechanisms for mobilizing funding for infrastructure investments from the private sector, land leasing and sales (Chapter 10) and private participation in infrastructure operations (Chapter 11).